Romania: Development of Labor Law Under the Banner of Flexibility - Vallasek, Magdolna (Fundamentals of Labor Law in Central Europe, 2022)
The last decade of Romanian labor law has been marked by a series of innovations and amendments under the banner of flexibility. In the case of both individual and collective labor law, the acceleration in the introduction of more flexible regulatory elements has been caused by the economic crisis that started after 2006, although there are also strong voices in the literature that the reference to the global economic crisis is not always tenable and has sometimes served as a good excuse for introducing certain legislative changes. In this chapter, we present the current regulation of individual and collective employment contracts, together with its theoretical and practical issues, starting from the specificities of the development of Romanian labor law.Keywords: labor law, labor contract, collective agreement, flexicurity, Romania